2021
DOI: 10.1177/0306624x211066825
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Offenders With Intellectual Disabilities: An Exploratory Comparison Study in an Incarcerated U.S. Sample

Abstract: Research indicates that individuals with intellectual disabilities (ID) are overrepresented among sexual offenders, and that those with ID might differ from those without ID in terms of the etiology of offending behavior. Despite this, few studies have explored ID using incarcerated U.S. samples. The present study sought to identify relevant characteristics of this population by comparing individuals with and without ID who are incarcerated in the U.S. for sexual offenses. Archival records for 3,066 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…When comparing 2220 people with intellectual disabilities and 2085 controls without intellectual disabilities, Nixon et al ( 2017 ) found that people with intellectual disabilities were more likely to have been charged and/or victimised with a sexual or violent offence than those without intellectual disabilities. Contrary to this finding, in a study among the incarcerated, Callahan et al ( 2022 ) found that people with intellectual disabilities were no more likely to commit sexual offences compared to people without this diagnosis. People with intellectual disabilities can sexually abuse others while simultaneously being victims of sexual abuse themselves (Lindsay et al, 2012 ).…”
Section: Introductionmentioning
confidence: 83%
“…When comparing 2220 people with intellectual disabilities and 2085 controls without intellectual disabilities, Nixon et al ( 2017 ) found that people with intellectual disabilities were more likely to have been charged and/or victimised with a sexual or violent offence than those without intellectual disabilities. Contrary to this finding, in a study among the incarcerated, Callahan et al ( 2022 ) found that people with intellectual disabilities were no more likely to commit sexual offences compared to people without this diagnosis. People with intellectual disabilities can sexually abuse others while simultaneously being victims of sexual abuse themselves (Lindsay et al, 2012 ).…”
Section: Introductionmentioning
confidence: 83%
“…People are often defined in services and society by their behaviour (i.e., sexual interest towards children), and we wanted to see the person behind the diagnosis, while balancing the reality of the risk and the reasons those circumstances have come upon him (i.e., care plan). Increasing our awareness on the high estimated prevalence of inappropriate sexual interests toward children and sexual offending in male adults with learning disabilities was helpful (Callahan et al, 2021; Craig et al, 2006). Research offers hypotheses including the absence of opportunities for age‐appropriate intimate relationships and lack of sex education (Lindsay, 2004; Lindsay & Parry, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Research on WBIs in general psychiatry suggests that usability is important for WBIs to work as intended (Petersen et al, 2019). As people with intellectual disabilities are overrepresented among individuals who have sexually offended (Callahan et al, 2022; Cantor et al, 2005), intellectual and learning disabilities could limit the understanding of the content of a WBI and therefore its effectiveness (Knaevelsrud et al, 2016). Also, language-based WBIs require reading skills and motivation, which can be a barrier for forensic clients with low education and low motivation (Drieschner & Boomsma, 2008).…”
Section: Development Of Wbis For Icsocmentioning
confidence: 99%